Insights into charge carrier dynamics in organo-metal halide perovskites: from neat films to solar cells. (3rd August 2017) - Peng, Jiajun; Chen, Yani; Zheng, Kaibo; Pullerits, Tõnu; Liang, Ziqi
Abstract : Various transport measurements for perovskites are reviewed with profound insights into charge dynamics from neat films to solar cells. Abstract : Organo-metal halide perovskites have recently obtained world-wide attention as promising solar cell materials. They have broad and strong light absorption along with excellent carrier transport properties which partially explain their record power conversion efficiencies above 22%. However, the basic understanding of the underlying physical mechanisms is still limited and there remain large discrepancies among reported transport characteristics of perovskite materials. Notably, the carrier mobility of perovskite samples either in thin films or within solar cells obtained using different techniques can vary by up to 7–8 orders of magnitude. This tutorial review aims to offer insights into the scope, advantages, limitations and latest developments of the techniques that have been applied for studying charge carrier dynamics in perovskites. We summarize a comprehensive set of measurements including (1) time-resolved laser spectroscopies (transient absorption, time-resolved photoluminescence, terahertz spectroscopy and microwave conductivity); (2) electrical transient techniques (charge extraction by linearly increasing voltage and time-of-flight); and (3) steady-state methods (field-effect transistor, Hall effect and space charge limited current). Firstly, the basics of the above measurements are described. We then comparatively summarize the charge carrier characteristics of perovskite-based neat films, bilayer films and solar cells. Finally, we compare the different approaches in evaluating the key parameters of transport dynamics and unravel the reasons for the large discrepancies among these methods. We anticipate that this tutorial review will serve as the entry point for understanding the experimental results from the above techniques and provide insights into charge carrier dynamics in perovskite materials and devices.